Islam the misunderstood religion - Rahman, Ahmed Abdel; Islamic Media Services (London : Islamic Media Services, 1988)
Interviews with Muslim converts as to why they convert and their experinces as a Muslim.
Islam the misunderstood religion - Remembering our duty - The hidden treasure - The Qur'an.
Keywords: Muslim converts